The promise of the East : Nazi hopes and genocide, 1939-43 - Ingrao, Christian 1970- (Polity, 2019)
"1939-1943, the Nazi imperial utopia started to take shape in the conquered areas of Eastern Europe, whose inhabitants were displaced, enslaved and murdered. This book examines for the first time the institutions and individuals behind this, revealing an aspect of Nazism often overlooked and shedding new light on how the Holocaust was realised"--